Strategies of School Citizens in the Success of School Based Management Programs (SBM) for Achieving School Quality - Karine Rizkita; Fitri Wulan Purnama; Khoirin Nur Hidayah; Mafelinda Yuliadita; Milanitaqwa Asri Pratiwi; Wyne Ristuti Priatna; Raden Bambang Sumarsono (Pedagogi: Jurnal Ilmu Pendidikan, 2021)
This study aims to see (1) the views of school members on the importance of school quality; (2) the role of school members in trying to achieve school quality; and (3) supporting factors for the school community in trying to achieve school quality. This research was conducted using a qualitative descriptive approach to obtain data in the field about the strategies of school members in the success of the SBM program in achieving school quality. Researchers conducted field studies and interviews with principals, vice-principals for curriculum, deputy principals of student affairs, and teachers of Islamic Religious Education (PAI). Apart from conducting interviews, researchers also conducted a documentation study at SMP Negeri 1 Bojonegoro as a research location. The results of the research found by researchers at SMP Negeri 1 Bojonegoro are as follows: (1) the views of the school community on the importance of school quality; (2) the role of school members in trying to achieve school quality; and (3) supporting factors for the school community in trying to achieve school quality